Kulturgeoraphie beobachtet. Probleme und Potentiale der geographischen Beobachtung von Kultur - Pott, Andreas (ERDKUNDE, 2005)
This article argues in favour of a cultural geography that builds on the notion of observation. Considering the problems of new cultural geography deriving from a missing theoretical differentiation between culture and society the need for a stronger reference to social theory becomes obvious. Following some ideas of social systems theory it is therefore suggested to reconceptualize culture as a pattern of observation. This makes it possible for cultural geography to apply a form of second order observation that pays special attention to the social context of mobilizing cultural distinctions and descriptions. Thus cultural geography is able to scrutinize where, how, why, and with what consequences the cultural form of observation is used and combined with spatial differentiations in modern society. The potential of this approach is demonstrated using examples from recent research.